P-20 A comparison of advance care planning before and during the COVID19 pandemic. (20th March 2022) - Atkinson, Kate; Spriggs, Helena; Frew, Katherine
Abstract : Background: The NICE guideline 'End of life care for adults: service delivery' states that services should offer advance care planning for those approaching the end of their life. 1 The COVID19 pandemic stimulated change across multiple services 2 ; this study considered the impact of the pandemic on advance care planning, specifically in the form of Do Not Attempt Cardio-Pulmonary Resuscitation (DNACPR) forms. Methods: A retrospective analysis of patients admitted in January 2020 and 2021, with a palliative care code (via Trust coding) on discharge or death. Results: The number of patients with a DNACPR on admission was consistent before and during the pandemic; 35% in 2020 and 39% in 2021. However, of those who did not have a DNACPR on admission, 90% had a new DNACPR on discharge during the pandemic, compared to 65% in 2020. In 2020 94% of patients discharged from a Specialist Palliative Care Inpatient Unit (SPCU) had a new DNACPR, compared to 93% during the pandemic. In 2020 on discharge from an acute hospital ward 45% of patients had a new DNACPR, almost doubling to 87% during the pandemic. Conclusions: Advance care planning, particularly DNACPR decisions, was documented more frequently during the COVID19 pandemic. In SPCUs advance care planning remained consistent before and during the pandemic. However, on acute hospital wards DNACPR decisions for inpatients with a palliative diagnosis were made more frequently. References: National Institute for Health and Care Excellence. (2019). End of life care for adults: service delivery [Nice Guideline No. 142] https://www.nice.org.uk/guidance/ng142 Gardner T, et al . (2020), Assessing the impact of COVID19 in 2020 and where next, The Health Foundation, [online], https://www.health.org.uk/publications/long-reads/elective-care-in-england-assessing-the-impact-of-covid-19-and-where-next